Existing barriers and recommendations of real-world data standardisation for clinical research in China: a qualitative study. Issue 8 (3rd August 2022) - Lai, Junkai; Liao, Xiwen; Yao, Chen; Jin, Feifei; Wang, Bin; Li, Chen; Zhang, Jun; Liu, Larry
Abstract : Objective: To investigate the existing barriers and recommendations of real-world data (RWD) standardisation for clinical research through a qualitative study on different stakeholders. Design: This qualitative study involved five types of stakeholders based on five interview outlines. The data analysis was performed using the constructivist grounded theory analysis process. Setting: Eight hospitals, four hospital system vendors, three big data companies, six medical products companies and four regulatory institutions were included. Participants: In total, 62 participants from 25 institutions were interviewed through purposive sampling. Results: The findings showed that the lack of clinical applicability in existing terminology standards, lack of generalisability in existing research databases, and lack of transparency in existing data standardisation process were the barriers of data standardisation of RWD for clinical research. Enhancing terminology standards by incorporating locally used clinical terminology, reducing burden in the usage of terminology standards, improving generalisability of RWD for research by using clinical data models, and improving traceability to source data for transparency might be feasible suggestions for solving the current problems. Conclusions: Efficient and reliable data standardisation of RWD for clinical research can help generate better evidence used to support regulatory evaluation of medical products. This research suggested enhancing terminology standards by incorporating locally used clinical terminology, reducing burden in the usage of terminology standards, improving generalisability of RWD for research by using clinical data models, and improving traceability to source data for transparency to guide efforts in data standardisation in the future.